2009
DOI: 10.1007/s00127-009-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Family factors and children’s disruptive behaviour: an investigation of links between demographic characteristics, negative life events and symptoms of ODD and ADHD

Abstract: Even in an affluent and egalitarian society, children's life circumstances are related to their mental health. Further, there seems to be some specificity in the demographic risk factors associated with ODD and with ADHD symptoms, while negative life events act as general stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 49 publications
4
54
2
1
Order By: Relevance
“…With regard to the characteristics of the family environment, ADHD has been found to be more common among children reared in families experiencing adversity such as marital discord, low socio-economic status, large family size, paternal criminality, and maternal mental disorder [44,51,52,70]. ADHD has also been found to be related to negative parent-child relationships.…”
Section: Introductionmentioning
confidence: 97%
“…With regard to the characteristics of the family environment, ADHD has been found to be more common among children reared in families experiencing adversity such as marital discord, low socio-economic status, large family size, paternal criminality, and maternal mental disorder [44,51,52,70]. ADHD has also been found to be related to negative parent-child relationships.…”
Section: Introductionmentioning
confidence: 97%
“…However, the evidence that diagnoses and prescription of medication for mental health issues is proportionally higher in families who experience disadvantages of various kinds [62][63][64][65][66] lend moral weight to encouraging broader perspectives than solely the medical when discussing emotional distress in children. As adults we need to strive for ethical and responsible actions that is in the best interest of children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that children from families facing various such disadvantages are diagnosed with ADHD more frequently than children who are not disadvantaged [62][63][64][65][66]. In a major study of more than a million school children in Sweden strong links were found between receiving medication for ADHD and poor maternal education, single parent families and welfare benefits [67].…”
Section: Introductionmentioning
confidence: 99%
“…al. 2003;McCabe, Butterfield, & Trevino, 2006;Rydell, 2010), little attention has been directed to student behaviors in the higher education setting. Instead, in an academic context it is more usual to research unethical behaviors such as cheating on exams or plagiarism (Smith & Davis, 2004;Sutherland-Smith, 2005;Gino, Schweitzer, Mead, & Ariely, 2011;Taradi, S. K., Taradi, M., & Đogaš, 2012).…”
Section: Comments In Class Mobile Phones In Class Doing As Little Amentioning
confidence: 99%